2012
DOI: 10.1007/s00128-012-0599-6
|View full text |Cite
|
Sign up to set email alerts
|

Use of Solen brevis as a Biomonitor for Cd, Pb and Zn on the Intertidal Zones of Bushehr–Persian Gulf, Iran

Abstract: The concentrations of Zn, Cd and Pb were determined in tissues (shell and soft tissue) of 144 of bivalve mollusks (Solen brevis) and 15 samples of surface sediment collected from three locations in intertidal zones of Bushehr coast, Persian Gulf, Iran in May 2011. The mean concentrations of Zn, Cd and Pb in the sediment samples were 26.2, 1.25, and 21.1 μg/g dw, respectively. The mean levels of Zn, Cd and Pb in the clam samples were 63.3, 0.67, and 4.38 μg/g dw in soft tissue and 10. 7, 1.53, and 15.6 μg/g dw … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In the previous studies, Dan et al (2014) and Hop et al (2017) observed the same situation at the Tan Thanh site. Some other studies investigated the nonsignificant statistical correlation between the metal concentrations in bivalve species and in their living environment (de Astudillo et al 2005;Madkour et al 2011;Salahshur et al 2012). Madkour et al (2011) presented that heavy metal accumulation in hard clams might not come directly from one source such as sediment but it could derive from other sources such as SPM or surface water.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, Dan et al (2014) and Hop et al (2017) observed the same situation at the Tan Thanh site. Some other studies investigated the nonsignificant statistical correlation between the metal concentrations in bivalve species and in their living environment (de Astudillo et al 2005;Madkour et al 2011;Salahshur et al 2012). Madkour et al (2011) presented that heavy metal accumulation in hard clams might not come directly from one source such as sediment but it could derive from other sources such as SPM or surface water.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported bivalves are important sources of nutrition [5,[11][12][13][14][15][16] as well as the potential to accumulate heavy metals [6,8,[17][18][19][20][21][22]. However, so far there is no publication regarding the nutrient content as well as the heavy metals content of Meretrix sp.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to their sedentary habit, manageable size, widespread distribution, and relative tolerance to xenobiotics, bivalve mussels are well suited as sentinels and are widely used for biomonitoring the aquatic environment (Englund and Heino, 1996;Kwan et al, 2003;Waykar and Shinde, 2011;Salahshur et al, 2012). The BEWS utilizing mussels is based on valvometry and relies on the tendency of bivalves to alter shell movements in response to toxicants and other stressful stimuli (Mosselmonitor, 2005).…”
Section: Introductionmentioning
confidence: 99%